PERAN ORANG TUA DALAM MENSTIMULASI PERKEMBANGAN BAHASA ANAK USIA DINI - Rani Endah Lestari; Rahma Handayani (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Language development in early childhood is a critical aspect in the formation of their cognitive, social and emotional abilities. The role of parents in stimulating this language development holds a central position and significantly influences the pattern of child development. Research shows that regular interactions between parents and children in the prepubescent to early childhood period are critical moments in forming the foundations of language. Parents have several key roles in helping children develop language. First, they serve as the primary models of everyday language use. Through rich and varied verbal interactions, children learn vocabulary, grammatical structures and essential communication skills. Next, parents also play a role in creating a supportive environment for language learning, including reading books, singing songs and telling stories to their children. These activities broaden children's exposure to language and stimulate their imagination and creativity. In addition, parents also play a role in responding positively to children's communication efforts. Listening attentively, providing positive feedback, and stimulating responses to children's speech are important. This encourages children's confidence in speaking and interacting. Last but not least, parents should understand that each child has a different pace and way of learning. Therefore, recognition of children's uniqueness and individual development and patience in helping them overcome difficulties are key in supporting optimal language development. In conclusion, the role of parents in stimulating early childhood language development is crucial. By modeling, creating a supportive environment, responding positively and understanding the uniqueness of each child, parents can play a vital role in forming a strong language foundation for their children.